BIOLOGICAL ASSET MANAGEMENT: FAIR VALUE AND LIVESTOCK OF PSAK 69 - Putra, Indra Lukmana; Puspitasari, Peni; Nugrahani, Novi; Imam, M. Kholisul; Rohim, Yasin Nur (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2025)
Investigates the role of biological asset management in advancing Indonesia’s strategic goal of food self-sufficiency. It emphasizes the livestock sector's contribution to agrarian economic growth and the Sustainable Development Goals (SDGs), focusing on the implementation of PSAK 69. Employing a qualitative approach, the study utilizes case studies and financial data analysis to assess how PSAK 69 influences the valuation of biological assets, managerial decision-making, and financial performance in the livestock industry. Findings reveal that PSAK 69 significantly enhances financial transparency, enabling more accurate recognition and measurement of biological assets. This improvement supports better-informed managerial policies and strengthens both local industry performance and integration into global markets. The study offers original insights into the intersection of financial reporting standards and sustainable agricultural practices, highlighting PSAK 69’s role in aligning asset management with food security and economic goals. However, limitations include the dynamic nature of livestock operations and limited long-term data on asset management outcomes. The implications are vital for policymakers and stakeholders seeking to enhance the strategic and economic resilience of Indonesia’s livestock sector within a sustainable development framework